Notes toward a theory of multilevel governing in Europe - Fritz W. Scharpf (Max-Planck-Institut für Gesellschaftsforschung, 2000)
The complexity of the multi-level European polity is not adequately represented by the single-level theoretical concepts of competing 'intergovernmentalist' and 'supranationalist' approaches. By contrast, empirical research focusing on multilevel interactions tends either to emphasize the uniqueness of its objects, or to create novel concepts - which are likely to remain contested even among Europeanists and have the effect of isolating European studies from the politicalscience mainstream in International Relations and Comparative Politics. These difficulties are bound to continue as long as researchers keep proposing holistic concepts that claim to represent the complex reality of the European polity as a whole. It is suggested that the present competition among poorly fitting and contested generalizations could be overcome if European studies made use of a plurality of simpler and complementary concepts, each of which is meant to represent the specific characteristics of certain subsets of multi-level interactions - which could also be applied and tested in other fields of political-science research. The paper goes on to describe four distinct modes of multi-level interaction in the European polity - 'mutual adjustment', 'intergovernmental negotiations', 'joint-decision making', and 'hierarchical direction' - and to discuss their characteristics by reference to the criteria of problem-solving capacity and institutional legitimacy. – – Die Komplexität der europäischen Mehrebenpolitik kann durch die auf Einebenen- Interaktionen zugeschnittenenen 'intergouvernementalen' oder 'supranationalen' Ansätze nicht adäquat repräsentiert werden. Die empirische Forschung betont deshalb entweder die Einzigartigkeit ihres Gegenstandes oder sie erfindet neuartartige Begriffe, die jedoch selbst in der Europaforschung umstritten bleiben und diese überdies von der theoretischen Diskussion in den Internationalen Beziehungen und der Vergleichenden Politikforschung isolieren. Diese Schwierigkeiten werden fortdauern, solange man versucht, die komplexe Realität der europäischen Politik jeweils im Ganzen durch holistische Begriffe zu erfassen. Die unergiebigige Konkurrenz zwischen umstrittenen Generalkonzepten könnte jedoch durch eine Mehrheit einfacherer und komplementärer Begriffe überwunden werden, die jeweils bestimmte Typen von Mehrebenen-Interaktionen bezeichnen - und die deshalb auch außerhalb der Europaforschung angewandt und überprüft werden können. Der vorliegende Vortragstext beschreibt vier solcher Typen - wechselseitige Anpassung, intergouvernementale Verhandlungen, Politikverflechtung und hierarchische Steuerung - und erörtert ihre charakteristischen Eigenschaften mit Bezug auf die Kriterien der Problemlösungsfähigkeit und der institutionellen Legitimität.
Keywords: 300